Prognostic factors in clinical stage I non-seminomatous germ-cell tumours of the testis. - Raghavan, D. (Nature Publishing Group, 1982)
Prognostic factors have been studied in 59 men with clinical Stage I non-seminomatous germ-cell tumours of the testis (NSGCTT) seen at the Royal Marsden Hospital between 1973 and 1978. Fourteen of the patients relapsed, and 45 have remained continuously disease-free. Two factors were identified which showed a significant correlation with relapse following radiotherapy: local extent of the primary tumour, and rate of decline of serum alpha-foetoprotein (AFP) and beta-human chorionic gonadotrophin (hCG) levels following orchidectomy. High serum marker levels at the time of referral after orchidectomy were not prognostically significant per se. The presence of tissue-associated hCG in the primary tumour was not prognostically significant. The results were compared with histology and pathological stage of the primary tumour in patients presenting with lung metastases but no clinical evidence of lymph-node disease. Embryonal carcinoma was more commonly associated with a locally invasive primary tumour and with extralymphatic spread than was teratocarcinoma.